TAFSSA District Agrifood Systems Assessment in India 2023: Community - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
TAFSSA (Transforming Agrifood Systems in South Asia) is a CGIAR Regional Integrated Initiative aimed at supporting actions that improve equitable access to sustainable healthy diets, enhance farmers’ livelihoods and resilience, and conserve land, air, and water resources in South Asia. The TAFSSA district agrifood systems assessment aims to provide a reliable, accessible, and integrated evidence base that links farm production, market access, dietary patterns, climate risk responses, and natural resource management with gender as a cross-cutting issue in rural areas of Bangladesh, India, and Nepal. It is designed to be a district-level multi-year assessment. Data were collected in March-April 2023 in the Nalanda district in India. Three respondents were interviewed per household: a female adult (aged 20+ years) primarily responsible for managing the household, a male adult (aged 20+ years) primarily responsible for agricultural activities, and an adolescent (aged 10-19 years). The assessment also included a community questionnaire, which interviewed a key informant in the district villages. The community questionnaire was conducted using pretested, structured questionnaires. Information was collected on village demographic composition, wage rates and machine rental costs during the agricultural season, infrastructure, and groundwater and land use.